A prediction model for high ovarian response in the GnRH antagonist protocol - Jiang, Yilin; Cui, Chenchen; Guo, Jiayu; Wang, Ting; Zhang, Cuilian (Frontiers in Endocrinology, 2023)
Backgrounds: The present study was designed to establish and validate a prediction model for high ovarian response (HOR) in the GnRH antagonist protocol.Methods: In this retrospective study, the data of 4160 cycles were analyzed following the in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI) in at our reproductive medical center from June 2018 to May 2022. The cycles were randomly divided into a training cohort (n=3121) and a validation cohort (n=1039) using a random sampling method. Univariate and multivariate logistic regression analyses were used to screen out the risk factors for HOR, and the nomogram was established according to based on the regression coefficient of the relevant variables. The area under the receiver operating characteristic curve (AUC), the calibration curve, and the decision curve analysis were used to evaluate the performance of the prediction model.Results: Multivariate logistic regression analysis showed revealed that age, body mass index (BMI), follicle follicle-stimulating hormone (FSH), antral follicle count (AFC), and anti-mullerianmüllerian hormone (AMH) were independent risk factors for HOR (all P < 0.05). The prediction model for HOR was constructed based on these factors. The AUC of the training cohort was 0.884 (95% CI: 0.869-0.899), and the AUC of the validation cohort was 0.884 (95% CI:0.863-0.905).The prediction model can predict the probability of high ovarian response prior to IVF/ICSI treatment, helping enabling clinicians to better predict the risk of HOR and guide treatment strategies.